FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR INDUSTRI MAKANAN DAN MINUMAN DI BEI PERIODE 2017-2019 - Clara Mulia (Jurnal Akuntansi, 2021)
This study aims to test empirically the factors that affecting.the firm’s.performance. The object of the research is a manufacturing company food and beverage industry listed on.Indonesia Stock.Exchange for the.period 2017 – 2019. The sampling uses purposive sampling methods with predefined criteria. Overall sample was 18 companies and 54 observational data. Data.analysis technique performed is multiple.linear regression. The result obtained in this.study there is enough evidence that the independent.board of.commissioners variables have a significant positive effect while the audit committee and the size of company have a significant negative.effect.on financial.performance.The results of this study are expected to be useful for users of the company’s..financial statement and investors .in. making final decisions and this study can contribute to future research. Keywords: Firm performance, Independent Board of Commisioners, Audit Committee, Size of Company. References: Effendi, M. A. (2017). The Power of Good Corporate Governance. Erawati, T., & Wahyuni, F. (2019). Pengaruh Good Corporate Governance, Ukuran Perusahaan Dan Leverage Terhadap Kinerja Keuangan Perusahaan Di Bursa Efek Indonesia ( Studi Kasus Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 ). 1(2), 129–137. Gunawan, I. ., Darmawan, N. A. ., & Purnamawati, I. G. . (2015). No Title. Jurnal Akuntansi Program S1 Universitas Pendidikan Genesha, 3. Hery. (2017). Kajian Riset Akuntansi (A. Pramono, ed.). PT. Grasindo. Kasih, A. P. (2014). Pengaruh Good Corporate Governance. Lestari, W. D., & Yulianawati, I. (2012). Pengaruh Good Corporate Governance Dan Leverage Terhadap Kinerja Keuangan ( Studi Pada Perusahaan Manufaktur Yang Terdaftar BEI Tahun 2011 - 2012). 127–135. Nofitasari, N. (2015). Pengaruh good corporate governance dan kinerja perusahaan terhadap nilai perusahaan (studi pada badan usaha milik negara yang terdaftar di bursa efek indonesia tahun 2010 - 2013). Jurnal Administrasi Bisnis, 25, 108–117. Novitasari, D. P. (2016). Pengaruh Mekanisme Good Corporate Governance Terhadap Kinerja Keuangan. 106–119. Purwani, T. (2001). Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan. Rahmawati, I. A., Rikumahu, B., & Dillak, V. J. (2017). Pengaruh Dewan Direksi, Dewan Komisaris, Komite Audit dan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan. 2(2), 54–70. Sarafina, S., & Saifi, M. (2017). Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Dan Nilai Perusahaan ( Studi pada Badan Usaha Milik Negara ( BUMN ) yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015 ). 50(3), 108–117. Scott, W. R. (2015). Financial Accounting Theory (7th ed.). Ula, F., Sochib, & Ermawati, E. (2018). Pengaruh Ukuran Perusahaan Dan Stuktur Kepemilikan Publik Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI. Progress Conference Vol. 1, No. 1, 1(1), 861–869.